Cadherins: cellular adhesive molecules serving as signalling mediators. (8th August 2018) - Yulis, Mark; Kusters, Dennis H. M.; Nusrat, Asma
Abstract: The single pass, transmembrane proteins of the cadherin family have been appreciated as important proteins that regulate intercellular adhesion. In addition to this critical function, cadherins contribute to important signalling events that control cellular homeostasis. Many examples exist of classical, desmosomal and atypical cadherins participating in the regulation of signalling events that control homeostatic functions in cells. Much of the work on cadherin mediated signalling focuses on classical cadherins or on specific disease states such as pemphigus vulgaris. Cadherin mediated signalling has been shown to play critical roles during development, in proliferation, apoptosis, disease pathobiology and beyond. It is becoming increasingly clear that cadherins operate through a range of molecular mechanisms. The diversity of pathways and cellular functions regulated by cadherins suggests that we have only scratched the surface in terms of the roles that these versatile proteins play in signalling and cellular function. Abstract : Modalities of cadherin mediated signalling. Cadherins have been shown to participate in many diverse signalling pathways and mechanisms. Not only is the range of functional outcomes that cadherins regulate wide, the number of different types of mechanisms that cadherins participate in to mediate their signalling is also impressive. Many times cadherins themselves act as scaffolds for important signalling events and the ability of the cadherin to participate in these signalling mechanisms is often dependent upon their participation in cadherin mediated adhesion ( A ). Other mechanisms requiring cadherin mediated adhesion include cadherin protein association with other transmembrane signalling proteins and receptors ( B ). There are several reports of cadherin mediated signalling that requires the formation of stable cadherin protein fragments via regulated proteolytic cleavage ( C and D ). Most of these mechanisms require cadherin extracellular fragment generation and often both stimulate receptor signalling pathways and interfere with cadherin mediated adhesion ( C ). There are, however, multiple studies describing cadherin intracellular protein fragment generation ( D ). These mechanisms often entail binding of the intracellular fragment to a cytoplasmic signalling partner, nuclear re‐localization, and regulation of gene transcription.